Underlying structure of the system, based on the behavior of the dynamic system. - Castañeda Marín, Hernando; Rodríguez Graterol, Wladimir; Colina Morles, Eliézer (Computers and Simulation in Modern Science, Volume I, 2008)
The main motivation of this paper is to develop some methods or techniques that will allow us to study complex systems (in the sense of finding their underlying structure or their similarity to others). If we have these techniques, we will be able to tackle a series of real life problems that until now have found no reliable solution. Examples of such problems are 3D-object recognition, handwritten word recognition, interpretation of bio-medical signal and speech recognition. In this paper, we will present a technique to analyze dynamical systems based on their behavior, where that behavior can be determined from the system output trajectories. We will use dynamic pattern recognition concepts for dynamic system analysis.
Keywords: Ciencias Computacionales; Ingeniería; Departamento de Computación; Facultad de Ingeniería; Pattern recognition; Dynamical system; Complex systems; Artificial Intelligence; Similarity; Artículos